Penerapan Keselamatan Dan Kesehatan Kerja Di Industri Farmasi PT X - Elsa Elvina; Sri Mulyeni (Lembaga Pengembangan Kinerja Dosen, 2024)
This research uses a qualitative descriptive approach through case studies in conducting accident risk analysis in the pharamaceutical industry and to fully and deeply understand the procedures for implementing Occupational Health and Safety at PT X. the technique used in this research is through a questionnaire distributed to respondents. Nased on the results of questionnaires from employees, it was concluded that PT X had implemented Occupational Safety and Health (K3) procedures well. This is proven by the existence of socialization and training in Occupational Safety and Health procedures as an effort to protect all employees from the risk of accidents. The company also equips all employees with Personal Protective Equipment (PPE) to protect employees from the risk of work accidents. Apart from that regular monitoring and evaluation is also carried out, to ensure that the procedure is still suitable to be implemented. The work environment plays a role in the safety and health of workers. Worker attitudes and work procedures that have been implemented by all employees have a very important role in Occupational Safety and Health as an effort to minimize accidents.